Self- assembly of isomannide-based monoesters of C18-fatty acids and their cellular uptake studies - Dhasaiyan, Prabhu; Parekh, Nimisha; Reddy, T. Vijai Kumar; Rani, G. Sandhya; Devi, B. L. A. Prabhavathi; Bhagavatula L. V. Prasad (RSC Advances, 2016)
The self-assembling behavior of oleic, elaidic and stearic acid-isomannide glycolipids is revealed. Amongst these, oleic and elaidic acid-based isomannide lipids self-assembled to form microspheres which were efficiently taken up by cancer cell lines enabling their usage for drug delivery applications.